THE DETERMINANTS OF THE DEMAND FOR INTERNATIONAL RESERVES IN MEXICO: A VECTOR ERROR CORRECTION MODEL - GARZA-RODRIGUEZ, Jorge; GONZALEZ-GAMEZ, Luis F.; IZAGUIRRE-MONSIBAIZ , Benjamin; NADER-DELEON , Daniel A.; TREVIÑO-CARRILLO, Erick H. (Journal of Advanced Studies in Finance, 2016)
The objective of this research was to identify the determinants of international reserves in Mexico. Using a Vector Error Correction Model, it was found that foreign portfolio investment has a significant positive effect on the demand for reserves both in the short run as in the long run. A decrease in the average propensity to import causes an increase in the demand for reserves in the long run, while in the short run the effect is the opposite. On the other hand, the long-term effects of exchange rate volatility, short-term external debt and the opportunity cost on the demand for reserves are statistically significant only in the short run but not in the long run. It was concluded that the demand for international reserves in Mexico can be explained in the long run by the marginal propensity to import and indirect foreign investment, while in the short run it can be explained by the volatility of the exchange rate, the average propensity to import, short-term external debt, the opportunity cost of reserves and by monetary imbalances.